Perlindungan Konsumen Terhadap Praktek Monopoli - Wally, Iwan; Suharyanto, Didik; Tio Rae, Crodios Nyoman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. This law was formed to encourage the creation of economic efficiency and an equal business climate for all business actors. Legal research is a scientific activity based on certain methods, systematics and thoughts that aim to study one or several specific legal phenomena by analyzing them. The research method used in the thesis research is the normative legal method. In this study, field and library materials are basic research data that are classified as secondary data. Cartel practices in the distribution of cooking oil in Indonesia meet the elements of a cartel as regulated in Article 11 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, namely the element of intending to influence prices, the element of regulating production and/or marketing, the element of goods, the element that can result in monopolistic practices, and the element that can result in unfair business competition. However, of the nine elements of cartel practices that have been fulfilled, it cannot be said that it has been proven to have carried out cartel practices, and there has been a decision in case 15/KPPU-I/2022 by the KPPU regarding cartel practices that have resulted in unfair business competition.